2017
DOI: 10.1073/pnas.1705240114
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Presenilin 1 decreases β-amyloid by facilitating autophagosome–lysosome fusion

Abstract: Presenilin 1 (PS1), the catalytic subunit of the γ-secretase complex, cleaves βCTF to produce Aβ. We have shown that PS1 regulates Aβ levels by a unique bifunctional mechanism. In addition to its known role as the catalytic subunit of the γ-secretase complex, selective phosphorylation of PS1 on Ser367 decreases Aβ levels by increasing βCTF degradation through autophagy. Here, we report the molecular mechanism by which PS1 modulates βCTF degradation. We show that PS1 phosphorylated at Ser367, but not nonphospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 33 publications
3
66
0
Order By: Relevance
“…Lack of phosphorylation on PS1 1 Ser367 impedes the fusion of autophagosome and lysosome in mouse brain. And then, this inhibition of autophagy reduced βCTF degradation leading to the accumulation of Aβ in the brain . These observations imply that PS1 could be a promising target for the treatment of AD through autophagy.…”
Section: Autophagy and Alzheimer's Diseasementioning
confidence: 81%
“…Lack of phosphorylation on PS1 1 Ser367 impedes the fusion of autophagosome and lysosome in mouse brain. And then, this inhibition of autophagy reduced βCTF degradation leading to the accumulation of Aβ in the brain . These observations imply that PS1 could be a promising target for the treatment of AD through autophagy.…”
Section: Autophagy and Alzheimer's Diseasementioning
confidence: 81%
“…Autophagy failure is commonly implicated in the pathological characteristics of AD 17 20 . Increasing evidences support that the function of PS1 affects autophagy process 21 25 . Serious impaired autophagy phenotypes such as accumulation of autophagic vacuoles and lysosomal dysfunction are observed in PS1-knockout mouse blastocysts, PS1-knockout mouse neurons, and mice brains with reduced levels of PS1 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Out of the mass spectrometry hits, found in two independent replicates, AnnexinA2 (human ANXA2) increased its affinity for LRRK2 upon α-syn PFF treatment. Intriguingly, ANXA2 is a phospholipid-binding protein that intervenes in phagocytic processes at multiple levels [56][57][58][59][60][61][62]. Specifically, it was reported that AnxA2 deficits are linked to a decreased endocytosis and particle internalization [56,63,64].…”
Section: Lrrk2 Interacts With Anxa2mentioning
confidence: 99%